Faktor - Faktor yang Mempengaruhi Kesiapsiagaan Perawat dalam Menghadapi Bencana Banjir di Kecamatan Gumukmas Kabupaten Jember (Factors Influencing Nurse Preparedness in the Face of Flooding in Gumukmas District in Jember) - Dewi Amaliyah Wahidah; Rondhianto Rondhianto; Mulia Hakam (Pustaka Kesehatan, 2016)
Preparedness is activities which is being undertaken to anticipating disaster to well organize. Nursehas responsibility to manage disaster to minimize the impact of disaster. There are many factors(age, years in nursing, previous experience with disaster situation, worked in a post disaster shelter,self regulation and health care climate) influence nurse to take well preparedness. The objective ofthe research is to analyze the factors influence preparedness. The descriptive analitic with crosssectional approach. The sample of the research are 16 nurses. The data taken using questionnairefrom Emergency Preparedness Information Questionnaire that have been modiefied. The analyze ofdata using spearman rho test and logistic regression (with α = 0,05). The result of bivariat analyzethere are significant relations between age, years in nursing, previous experience with disastersituation, worked in a post disaster shelter, self regulation, health care climate with preparedness (p< α = 0,05). From multivariat analyze we know that years in nursing is variable dominan factor thatinfluence nurse preparedness (p = 0,020 < α = 0,05). The result indicated that years in nursing ofthe nurse preparedness to face disaster.Keywords : Preraredness nurse, manage disaster, flooding